Antecedent of Consumer Impulsive Buying Behavior: A perspective of Developing Nation - Mishra, Ugdam (Journal of Research and Development, 2021)
Impulsive buying concerns the unplanned decision made by consumers before buying any items. Recognizing the factors that influence consumer’s impulsive buying behavior aids retail stores to understand consumer’s decision-making process and accordingly help them design and develop courses of action. However, few studies have only been conducted in this area in context of developing nation. The purpose of this study is to identify the factors that influence impulsive buying behavior and the vital factor amongst them. After collecting 141 valid responses, the study validated the proposed conceptual model using structural equation model. AMOS 26 was used to analyze the data. Data were analyzed in two-fold: Measurement model and structural model. Three items were covaried to reach the optimal model fit revealing hedonic value and shopping enjoyment significant influence on impulsive buying. This research contributes to the knowledge about the relationship among hedonic value, marketing stimuli, shopping enjoyment and social interaction with impulsive buying behavior.